An exploration of happiness within the Irish LGBTI community. Issue 1 (2nd January 2020) - de Vries, Jan M. A.; Downes, Carmel; Sharek, Danika; Doyle, Louise; Murphy, Rebecca; Begley, Thelma; McCann, Edward; Sheerin, Fintan; Smyth, Siobháin; Higgins, Agnes
Abstract: This paper explores factors which contribute to happiness among lesbian, gay, bisexual, transgender and intersex (LGBTI) individuals as part of the largest study to date of mental health in the LGBTI community in the Republic of Ireland (LGBTIreland study). This mixed methods study informed by minority stress theory, contained an online survey (n = 2, 264) which explored various aspects of mental health and distress, but also the extent and experience of happiness and concomitant factors. The survey included ratings of happiness and life-satisfaction and an open-ended question on LGBTI related happiness. Quantitative findings showed a mean happiness rating of 6.58 out of 10 (11-point scale), which is lower than the general population in Ireland. Those identifying as gay men or lesbian women rated their happiness significantly higher than bisexual, transgender, or intersex participants. There was also an effect for age: teenage LGBTI participants had significantly lower ratings than other age groups. Happiness ratings very highly correlated with life-satisfaction (.88). A multiple linear regression showed happiness was predicted most significantly by self-esteem and being in a relationship. Qualitative findings emphasized the importance of self-acceptance and peer support for happiness. Findings are discussed using the minority stress perspective and cognitive dissonance theory.